Nuclear Suppliers Group and Nuclear-Weapon-Free Zone: A Case for Pakistan - Mr. Khusrow Akkas Abbasi; Mr. Sajid Aziz (CISS Insight Journal, 2016)
Nuclear Supplier Group was formed in 1975, in response to Indian nuclear test in 1974, with the goal of regulating nuclear exports so as to disallow states to divert nuclear material and technology for making nuclear weapons. With the passage of time, the Group evolved, its members increased and it developed a membership criteria (discussed below). The criteria, inter alia, included the ability of a state to supply items covered by annexes of the NSG Guidelines and full compliance with the obligations as signatory of one or more of the following: The Treaty on the Non-Proliferation of Nuclear Weapons (NPT), or complying with one of the Nuclear-Weapon-Free Zones (NWFZs). Though signing NPT may not be in Pakistan’s national interest, the question of NWFZ is worth pondering over. This paper specifically deals with this question: Can Pakistan become part of any of the NWFZs? Does a legal ground exist? This requires not only a perusal of NSG criteria, but also demands a comparative analysis of the Treaty texts and their respective protocols. The first part of the paper discusses very briefly about NSG and the dominant rationale behind its formation. The second part contains an analysis of the treaty texts and their relevant protocols to determine whether there exists a legal case for Pakistan to become part of any of the NWFZs.